Radical uncertainty: Sources, manifestations and implications - Christian Müller (Kiel Institute for the World Economy (IfW), 2015)
This paper argues that radical uncertainty is the outcome of standard market activity. The theoretical findings are corroborated with empirical analyses. The model example is applied to asset pricing and radical uncertainty is found a solution to various asset pricing "puzzles". In conclusion, radical uncertainty should form the basis of economic analysis.
Keywords: F31; F47; C53; 330; rational expectations; uncertainty; subjectivity